Optimalisasi Potensi Desa Rawi Melalui Pembuatan Website Berbasis Teknologi Digital Dan Ekonomi Kreatif - Swissia, Pebrina; h, Halimah; Marshella, Ochi (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Rawi Village, located in Penengahan District, South Lampung Regency, possesses great potential in agriculture, localculture, and micro, small, and medium enterprises (MSMEs) that play a significant role in the village’s economy.However, the limited use of digital technology and the absence of an integrated information platform have resulted in thevillage’s potential not being widely recognized and public information dissemination remaining ineffective. This communityservice activity was carried out to support digital transformation in Rawi Village through the development of a VillageWebsite as an official information medium, a platform for promoting local potential, and a tool to enhance governmenttransparency. The implementation involved collecting data and identifying village potentials, designing and developing awebsite based on an accessible digital platform, and providing training for village officials to independently manage andupdate content. The results showed an improvement in the knowledge and digital skills of village officials, as well asincreased awareness of the importance of utilizing online media as a means of public communication. The developed websitenow serves as an information center containing the village’s profile, history, and potential, while strengthening the village’simage as a community that adapts well to technological advancement. Through this initiative, Rawi Village is expected tocontinue its transformation toward becoming an informative, independent, and sustainable digital village.